Electrospinning and Cyclodextrin Inclusion Complexes: An Emerging Technological Combination for Developing Novel Active Food Packaging Materials - Guarda-Moraga, A; Rodriguez-Mercado, F; Galotto-Lopez, M; Lopez de Dicastillo-Bergamo, A; Muñoz-Shuguli, C; Patiño-Vidal, C (Taylor and Francis Ltd., 2022)
This review was focused on describing the combination of electrospinning and cyclodextrin inclusion complexes as one of the newest alternatives for the development of food packaging materials with antimicrobial and/or antioxidant properties. The advantages of this technological combination, the routes to design the active materials, the characterization and application of such materials were reviewed. Electrospinning has allowed developing active packaging materials composed by fibrillary structures with a high ratio surface-to-volume. On the other hand, cyclodextrin inclusion complexes have maintained the properties of active compounds when they have been incorporated in packaging materials. Both methods have been recently combined and novel active food packaging materials have been obtained through three different routes. Polymeric solutions containing preformed (route 1) or in-situ formed (route 2) cyclodextrin inclusion complexes have been electrospun to obtain packaging materials. Furthermore, cyclodextrin inclusion complexes solutions have been directly electrospun (route 3) in order to produce those materials. The developed packaging materials have exhibited a high active compound loading with a long lasting release. Therefore, the protection of different foodstuff against microbial growth, oxidation and quality decay as well as the maintenance of their physical and sensory properties have been achieved when those materials were applied as active packaging. © 2021 Taylor & Francis Group, LLC.